LEADERSHIP STYLE OF MAHATHIR MOHAMAD: A SYSTEMATIC LITERATURE REVIEW - Razali, Nurul Aimi; Suhaimy, Khairul Azman Mohamad; Jaes, Lutfan; Othman, Hussain; Damin, Zahrul Akmal; Othman, Mohd Fuad; Lee Abdullah, Mohamad Ainuddin Iskandar (International Journal of Psychosocial Rehabilitation, 2020)
National leadership is a key element of the perpetual administration and development of a nation. Mahathir Mohamad is one example of an excellent national leader based on his leadership style. To date, no systematic review has been done on his leadership style. Therefore, this article aims to analyse the existing literature on the leadership style of Mahathir. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement, 11 related studies were identified from the Web of Science and Scopus databases as well as through direct handpicking of related sources. Further review of the articles through qualitative analysis ensued in nine core themes on Mahathir’s leadership, namely, people-oriented, resourceful, visionary, pragmatic, good communication skills, highly ethical, trustworthy, core value-based, and authentic. Meanwhile, there were a total of 22 sub-themes under these core themes. In general, Mahathir’s leadership style is holistic and his elements of leadership that are good and effective can be emulated and practised by individuals and leaders in their daily life. The findings can contribute to and empower the leadership field of study, particularly national leadership and good governance. Several recommendations are emphasised such as to conduct further quantitative or mixed methods studies, to highlight the theoretical or conceptual leadership frameworks employed in studies about Mahathir’s leadership, and to underscore the contribution of Mahathir’s leadership in the leadership field of study.